Achieving visible light excitation in carbazole-based Eu3+–β-diketonate complexes via molecular engineering. Issue 110 (23rd October 2015) - Francis, Biju; Heering, Christian; Freire, Ricardo O.; Reddy, M. L. P.; Janiak, Christoph
Abstract : A series of visible light excited Eu 3+ –carbazole based β-diketonate complexes has been developed by molecular engineering. Abstract : Herein, we present the synthesis, characterization and photophysical properties of a series of Eu 3+ complexes prepared with novel carbazole-based fluorinated β-diketones, namely, 4, 4, 5, 5, 5-pentafluoro-3-hydroxy-1-(9-phenyl-9 H -carbazol-2-yl)pent-2-en-1-one (L1 ) and 4, 4, 5, 5, 5-pentafluoro-3-hydroxy-1-(9-(4-methoxyphenyl)-9 H -carbazol-2-yl)pent-2-en-1-one (L2 ) as primary ligands and a bidentate phosphine oxide molecule, 4, 5-bis(diphenylphosphino)-9, 9-dimethylxanthene oxide (DDXPO) as ancillary ligand. Using the Sparkle/PM3 model the molecular geometries of the designed complexes are optimized and the luminescent parameters are calculated by the LUMPAC software. The results demonstrated that suitably expanded π-conjugation in the developed Eu 3+ –carbazole based β-diketonate complexes dramatically red-shifted the excitation maximum to the visible region ( λ ex, max = 420 nm) with an impressive quantum yield (34–42%). The triplet state energy levels ofL1 andL2 in the complexes are higher than that of the lowest excited level of Eu 3+ ion, 5 D0, so the photoluminescence mechanism of the Eu 3+ complexes was proposed as a ligand-sensitized luminescence process. The predicted luminescent parameters from the Sparkle/PM3 structures are in agreement with the experimental data, which shows the efficacy of the theoretical models adopted in the present study.